THE RELATIONSHIP BETWEEN REACTION TIME AND GAMING TIME IN E-SPORTS PLAYERS (Kinesiology, 2022)
E-sports can be defined as an electronic sports form and is growing at a rapid pace worldwide. E-sport requires high-speed reactions during all games. The purpose of this study was to evaluate auditory, visual and aim reaction times in different duration of game playing in e-sport players. Fifty-three participants were assigned into two groups according to their playing time which was either more or less than 14 hours per week. The participants were tested for auditory reaction time with online website at playback.fm, visual and aim reaction time on website of humanbenchmark.com. There were statistically significant differences in visual (p